2015
DOI: 10.1080/10408398.2012.760516
|View full text |Cite
|
Sign up to set email alerts
|

Walnuts (Juglans regia) Chemical Composition and Research in Human Health

Abstract: Walnuts are among the most widely consumed commercially grown tree nuts in the world. Many health benefits have been claimed for the consumption of these, including reduced risk of cardiovascular disease, coronary heart disease, type II diabetes treatment, and prevention and treatment of certain cancers, and the lessening of symptoms attributed to age-related and other neurological disorders. The health-promoting benefits of walnut consumption are ascribed to its fatty acid profile, which is rich in polyunsatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
87
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 153 publications
(88 citation statements)
references
References 114 publications
0
87
0
1
Order By: Relevance
“…It is a valuable lipid food source; indeed the oil content, ranging in commercial walnut varieties from 620 to 740 g kg −1 kernel, is the predominant component of this nut crop . Walnut oil is naturally rich in polyunsaturated fatty acids (PUFAs), mainly linoleic (55–70%) and linolenic (10–18%) acids, and is consequently poor in monounsaturated fatty acids (MUFAs), represented by oleic acid (10–20%), and in saturated fatty acids (SFAs) . Walnuts are mainly consumed as fruit, and their nutritional qualities and use depend mainly on their oil fatty acid profile.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is a valuable lipid food source; indeed the oil content, ranging in commercial walnut varieties from 620 to 740 g kg −1 kernel, is the predominant component of this nut crop . Walnut oil is naturally rich in polyunsaturated fatty acids (PUFAs), mainly linoleic (55–70%) and linolenic (10–18%) acids, and is consequently poor in monounsaturated fatty acids (MUFAs), represented by oleic acid (10–20%), and in saturated fatty acids (SFAs) . Walnuts are mainly consumed as fruit, and their nutritional qualities and use depend mainly on their oil fatty acid profile.…”
Section: Introductionmentioning
confidence: 99%
“…The development of alternative walnut oil feedstocks with improved functionality while maintaining nutritional quality has therefore become a priority for the food industry. The specific goal in walnut breeding could be improving the oxidative stability through reduction of PUFAs and relative increase of MUFAs . The objective of improved stability could be reached by raising the SFA content, but that can have adverse effects on human health due to the increase of low‐density lipoprotein (LDL) in blood caused by high palmitic acid (C16:0) consumption .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among all the nuts from the tree nut family, walnuts (Juglans regia) are the most enriched in PUFAs, with the highest ratio of omega-3:omega-6 (1:4.2). Walnuts also contain high levels of g-tocopherol, a form of vitamin E with proven anticancer benefit (9,12). A number of studies have identified beneficial effects of walnut consumption in a variety of diseases, including heart disease, diabetes, neurologic disorders, and cancer (9).…”
Section: Introductionmentioning
confidence: 99%
“…Nuts contain a large variety of beneficial bioactive components, including monounsaturated fatty acids (MUFA) and polyunsaturated fatty acids (PUFA) and contain only low amounts of saturated fatty acids (SFA), as well as a number of phytochemicals (i.e., phenolic antioxidants), dietary fiber, and minerals (9,10). PUFAs, including omega-3 fatty acids, reduce inflammation and have also been shown to lower polyp burden in animal models of colon cancer (11).…”
Section: Introductionmentioning
confidence: 99%